New lichenized and lichenicolous fungi for the Crimean peninsula (Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
Data on 25 species of lichenized and lichenicolous fungi new to the Crimean Peninsula, collected during Czech and Ukrainian-Czech lichenological excursions in June 2006 and May 2007 respectively, are provided. Among them, Arthonia lecanorina (Almq.) R. Sant., A. nideri (J. Steiner) Clauzade, Diederich & Cl. Roux, A. punctella Nyl., Caloplaca furax Egea et Llimona, C. soralifera Vondrák & Hrouzek, C. veneris Cl. Roux & Nav.-Ros., Carbonea assimilis (Körber) Hafelner & Hertel, Catillaria aff. scotinodes (Nyl.) Coppins, Endococcus macrosporus (Arnold.) Nyl., E. ramalinarius (Lind.) D. Hawksw., Fuscidea gothoburgensis (H. Magn.) V. Wirth & Vĕzda, Lichinella cribellifera (Nyl) P.P. Moreno & Egea, Milospium graphideorum (Nyl.) D. Hawksw., Phaeospora lecanorae Eitner, Placidium pilosellum (Breuss) Breuss, Verrucaria biatorinaria Zehetl, and V. poeltiana Clauzade & Cl. Roux are new to Ukraine. Caloplaca irrubescens (Nyl. ex Arnold) Zahlbr., Lecanora rouxii S. Ekman & Tønsberg, Lichenothelia scopularia (Nyl.) D. Hawksw., Melanelia hepatizon (Ach.) A. Thell, Peltigera collina (Ach.) Schrad., Staurothele areolata (Ach.) Lettau, Stigmidium rouxianum Calatayud & Triebel and Zwackhiomyces coepulonus (Norm.) Grube & R. Sant. are new to Crimea.
Keywords: Arthonia, biodiversity, Caloplaca, Crimea, lichenized fungi, lichenicolous fungi, Ukraine.